2016
DOI: 10.1155/2016/5137289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antileishmanial Activities of Acridines Derivatives against Promastigotes and Amastigotes Form of Parasites Using Quantitative Structure Activity Relationship Analysis

Abstract: In a search of newer and potent antileishmanial (against promastigotes and amastigotes form of parasites) drug, a series of 60 variously substituted acridines derivatives were subjected to a quantitative structure activity relationship (QSAR) analysis for studying, interpreting, and predicting activities and designing new compounds by using multiple linear regression and artificial neural network (ANN) methods. The used descriptors were computed with Gaussian 03, ACD/ChemSketch, Marvin Sketch, and ChemOffice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…The relationship obtained using this method corresponds to the linear combination of these descriptors (Table 3) It is observed that the coefficient of correlation r is high and the MSE is low, which makes it's possible to indicate that the model is more reliable. A p-value much smaller than 0.05 indicates that the regression equation is statistically significant, we can conclude, with confidence, that the model provides a significant amount of information 11 .…”
Section: Multiple Linear Regressions (Mlr)mentioning
confidence: 59%
See 2 more Smart Citations
“…The relationship obtained using this method corresponds to the linear combination of these descriptors (Table 3) It is observed that the coefficient of correlation r is high and the MSE is low, which makes it's possible to indicate that the model is more reliable. A p-value much smaller than 0.05 indicates that the regression equation is statistically significant, we can conclude, with confidence, that the model provides a significant amount of information 11 .…”
Section: Multiple Linear Regressions (Mlr)mentioning
confidence: 59%
“…Multiple linear regression (MLR) is used to study the relationship between a dependent variable and several independent variables; it minimizes the differences between actual and predicted values and has been used to select the descriptors to be used as inputs in multiple non-linear regression (MNLR) and artificial neural network ANN. Linear and non-linear approaches were used to predict the effects on the linear retention indices, the equations were justified by the correlation coefficient (r), the mean square error (MSE), the fisher value (F) and the significance level (p) 11 . MLR, MNLR and ANN are generated using the SPSS 19.0 statistical package 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal Component Analysis (PCA) [52] and Hierarchical Ascending Classification (HAC) [53,54], implemented in XLSAT software [55], were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Using these new variables, the dimensionality of the system is reduced with a minimum loss of information 15 . The obtained matrix of coordinates allows us to analyze the dispersion of individuals in the new defined space [16][17][18] . After that, the principal component analysis (PCA) was used to determine the non-linearity and nonmulticollinearity among variables and to select descriptors that correlate with the activity.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%